2011
DOI: 10.1002/dat.20508
|View full text |Cite
|
Sign up to set email alerts
|

The association of red blood cell parameters with mortality in a population of hemodialysis patients

Abstract: BBACKGROUND AND OBJECTIVESThe targeting of higher hemoglobin levels leads to increased cardiovascular events in patients with renal disease. This study is an attempt to discover if changes in red blood cell parameters are induced by erythropoiesis‐stimulating agents, and whether these changes are associated with mortality.METHODSA retrospective study of patients on hemodialysis at two dialysis units operated by Our Lady of Lourdes Hospital, Camden, N.J., evaluating the effect of dosage of epoetin alfa on red b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…This finding is consistent with findings of Peng et al 31 , in incident peritoneal dialysis patients, MCV was not statistically significantly associated with mortality in the fully adjusted model, and is consistent with findings of Chen et al 32 among haemodialysis patients, where the two year survival rate was significantly lower in the high red cell distribution width group, Balta et al 33 , found lower death rate among patients with higher MCV, though his cohort were patients with myocardial infarction. This finding is in contrast to findings by Hsieh et al among stage 3–5 CKD patients 34 , Sun et al among peritoneal dialysis patients in Korea, Brain et al 35 and Vashistha et al 36 among haemodialysis patients. The differences in results between our study and other studies may partly be explained by differences in patient characteristics, race, and diverse healthcare delivery systems.…”
Section: Discussioncontrasting
confidence: 91%
“…This finding is consistent with findings of Peng et al 31 , in incident peritoneal dialysis patients, MCV was not statistically significantly associated with mortality in the fully adjusted model, and is consistent with findings of Chen et al 32 among haemodialysis patients, where the two year survival rate was significantly lower in the high red cell distribution width group, Balta et al 33 , found lower death rate among patients with higher MCV, though his cohort were patients with myocardial infarction. This finding is in contrast to findings by Hsieh et al among stage 3–5 CKD patients 34 , Sun et al among peritoneal dialysis patients in Korea, Brain et al 35 and Vashistha et al 36 among haemodialysis patients. The differences in results between our study and other studies may partly be explained by differences in patient characteristics, race, and diverse healthcare delivery systems.…”
Section: Discussioncontrasting
confidence: 91%
“…Higher MCHC level, which reflects the concentration of hemoglobin in a red blood cell, is another factor that significantly contributes to the increased survival time. According to the vast literature review of ours, there was only one study on patients with ESRD which indicated that low MCHC is associated with lower short term survival [15]. Tennankore et al found that macrocytosis is associated with mortality in stable HD patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…This study also establishes other effective red cell parameters to distinguish LID from IDA or vice versa as shown in Table 2. The biochemical parameter, serum (ACD) from IDA Other research groups have also considered the utilization of various red cell parameters in characterizing hematological diseases, such as nonsickling hemoglobinopathy [26], chronic nephropathies [27], and even mortality in subjects undergoing hemodialysis [28]. In the future, simple algorithms may even be formulated by arithmetically incorporating more than one routine or eRBC parameters to achieve better distinction between 2 conditions of interest with the aid of ROC curves.…”
Section: -Specificitymentioning
confidence: 99%